Weaponized interdependence versus economic sanctions: The case of human rights abuses in Xinjiang Uyghur Autonomous Region - Emilian-Marian Stoica (CES Working Papers, 2022)
The situation of the human rights abuses in the Xinjiang Uyghur Autonomous Region (XUAR) is frequently reported in the Western media and it has gained a central place in the Euro-Atlantic political discourse which condemns Beijing's attitude towards human rights at home. However, the sanctions adopted by both the US and the EU in relation to the treatment applied by the Chinese government to the Uyghurs in the XUAR are strongly discouraged and limited by the economic dependencies of the two Western giants on China. The goal of this paper is to discuss the effectiveness of the economic sanctions in supporting the human rights international regime in the context of current economic interdependence between the European Union (EU) and the United States (US), on one side, and China, on the other side. The hypothesis of the paper is that the asymmetrical economic interdependence is undermining the effectiveness of the economic sanctions in supporting the human rights international regime. When there is an increased interdependence between a supporter and promoter of human rights, in this case the US and the EU, and a great economic power that does not regard the human rights as having a universal value in the current international order, the effects of the economic sanctions are inefficient in addressing this problem due to the high economic and political costs for both their issuers and their targets.
Keywords: 330; interdependence; economic sanctions; human rights; China